Can high-Tc superconductivity in cuprates be explained by the conventional BCS theory? - Božović, I.; Bollinger, A.T.; Wu, J.; He, X. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
For overdoped cuprates, it is believed that the normal state behaves as an ordinary Fermi liquid while the superconducting state conforms to the BCS theory. We have put these beliefs to the test by a comprehensive experiment in which over two thousand cuprate films were synthesized by molecular beam epitaxy and studied in great detail and precision. Here, we compare our key experimental results to various proposed explanations based on BCS theory extended to dirty d-wave superconductors, including the cases of strong (unitary) and weak (Born) scattering on impurities. The discrepancies seem insurmountable, and point to the need to develop the theory further, likely beyond the canonical BCS paradigm.